Education Interrupted: Enrollment, Attainment, and Dropout of Syrian Refugees in Jordan. Issue 9 (2nd September 2022) - Krafft, Caroline; Sieverding, Maia; Berri, Nasma; Keo, Caitlyn; Sharpless, Mariam
Abstract: The children affected by the Syrian conflict, including the large population of Syrian refugee children hosted in neighboring countries, are at risk of becoming a 'lost generation' due to interruptions in their schooling. This paper examines how educational outcomes of Syrian refugees in Jordan have evolved from pre-conflict to during conflict and displacement. We rely on nationally representative survey data from Jordan in 2016 and in-depth interviews with Syrian refugee youth. We use discrete-time hazard models and compare dropout pre-conflict, during the conflict, and during displacement for different stages of schooling. Syrian refugees in Jordan faced disrupted schooling in Syria due to the conflict, followed by several multidimensional supply- and demand-side barriers to education in Jordan. Yet ultimately enrollment rates, at least through 2016, have recovered to pre-conflict levels for basic education among the group of Syrians in Jordan, with important lessons for other countries struggling to protect refugee children's education. Host countries' policy response to refugee education plays a critical role in whether and for how long refugee children resume schooling after displacement.